Associative learning impairments in rats lacking dopamine transporter - A. A. Savchenko; I. M. Sukhanov; A. S. Ulitina; O. A. Dravolina; I. V. Belozertseva; A. K. Emelianov; E. E. Zvartau (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2022)
Introduction. Changes in the expression of the dopamine transporter (DAT) have been identified in patients with a number of neuropsychiatric disorders, but their significance for pathogenesis remains unclear. DAT knockout rats are a promising model of frontostriatal dysfunctions involved in adapting learning processes to current organism's needs, motivation, and experience.The objective was to evaluate the effect of DAT disruption on the interaction of classical and instrumental conditioning processes (associative learning).Methods and materials. Rats from a local colony were used: knockouts (n=31), heterozygotes (n=32), and wild type rats (n=24). DAT knockout (Slc6a3) was detected by PCR followed by restriction analysis. The rats were kept individually with limited access to food and unlimited access to water. In the operant chambers equipped with a MED-PC interface (MED Associates, USA), 3 experiments were performed: 1) classical conditioning; 2) autoshaping of operant responding; 3) reward learning based on secondary reinforcement. Statistical analysis was performed using SigmaPlot 12.5 (Systat Software Inc., USA) and SPSS Statistics 21 (IBM, USA).Results. We revealed that DAT disruption in rats did not affect the formation of conditioned reflex connections in classical conditioning (1) but was accompanied by impairments in the autoshaping of the operant response (2) and learning based on secondary reinforcement (3).Conclusion. The observed impairments of associative learning might be associated with a decreased incentive value of stimuli in hyperdopaminergic state.